Infrastructure Management and Construction - Sepasgozar, Samad M.E; Tahmasebinia, Faham; Shirowzhan, Sara (IntechOpen, 2020)
This book covers topics relevant to the concept of infrastructure construction, including key requirements of development such as measuring productivity and maintenance. It presents different categories of sustainability maintenance of critical infrastructures. In addition, it presents a complex simulation model, the reconfiguration simulator, which enables evaluation of the effectiveness of resilience enhancement strategies for electric distribution networks and the required resources to implement them. Then, it discusses health services as a critical sector in this field, which should be able to perform its function, even in times of crisis. The last chapter presents a brief review of different bridges, including the processes of design, material selection, construction, and maintenance.